FAMILY FORM OF NEPHROGENIC X-LINKED DIABETES INSUPLIUS - Ismoilov , Jamshid Abduraimovich; Egamberdiyeva , Yulduz Komiljon kizi; Mahmamuradova , Nargiza Negmatullayevna; Daminov , Abdurasul Takhirovich (Educational Research in Universal Sciences, 2024)
There is a global trend towards an increase in the prevalence of diabetes insipidus. Symptoms of nephrogenic diabetes insipidus (NDI) with X-linked inheritance appear in men and women with heterozygous mutations, and are characterized by an isolated symptom complex of polyuria, polydipsia, and hyposthenuria. In children, more often than in adults, when fluid is limited, a clinical picture of water deficiency dehydration develops with hypernatremia, hyperthermia and plasma hyperosmolality. This manuscript presents a case of NND, a familial form, X-linked in male patients. At the same time, in the female line of the family, the mother and grandmother also had an increased need for water; the use of minirin was ineffective. In the older and younger brothers, clinical manifestations of diabetes insipidus in the form of severe thirst and polyuria were noted from infancy; after examination, a diagnosis of diabetes insipidus was made and the drug desmopressin was prescribed. Due to the lack of effect from the use of desmopressin, an analysis of the exons and adjacent regions of the introns of the AQP2 and AVPR2 genes was carried out using the polymerase chain reaction method and subsequent direct sequencing. No mutations were identified in the AQP2 gene. A hemizygous substitution S315I was detected in the AVPR2 gene. The familial X-linked form of NND was confirmed. Hypothiazide is recommended, with constant use of which only slight positive dynamics are observed.